(NkI)QÇWSXKA rUSX(B: (NPO^ATKI UKRAÇNSXKOÇ DERVAWI (B:s)E (NPOS)QÆBNIK Z ÆSTORÆÇ (B/s)E - )Qæ(NWAN^ENKO(B, (NrAÇSA(B,s)E ((NkI)QÇW (B:s)E (NpROSW)QÆTA(B,s)E, 1995)
(Nw KNIZ)QÆ DOSLÆDVUÃTXSQ PERÆOD ÆSNUWANNQ kIÇWSXKOÇ rUSÆs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: )Qæ(NSTORÆQs)E -- )Qæ(NSTORÆQ uKRAÇNIs)E; (NkI)QÇWSXKArUSXs)E; (NDERVAWAs; (NRUSIs; (NkIJs; (NkI)QÃWI^Æs)E; (Nr@RIKOWI^)QÆs)E; (NkI)QÇWSXKA DERVAWAs)E